1.8 mW wideband LNA with double capacitor‐cross‐coupled feedback. Issue 20 (1st September 2014) - Wang, Zengqi; Li, Zhiqun; Shen, Changguo
Abstract : A 1.8 mW wideband common‐gate (CG) low‐noise amplifier (LNA) with double capacitor‐cross‐coupled (CCC) feedback is presented for multiband wireless communication standards. To achieve a low‐noise figure (NF) and high‐voltage gain under low power consumption, the CG LNA is based on the double CCC feedback and current‐reuse techniques. Post‐layout simulated results for 0.18 μm CMOS implementations show that the voltage gain is 18.1 dB with a 3 dB bandwidth from 100 MHz to 1.7 GHz and the IIP3 is −4.9 dBm at 1 GHz. The average NF is 2.4 dB within the entire 3 dB bandwidth. The LNA consumes 1.8 mW from a 1.8 V DC supply and the active size is 0.15 × 0.14 mm 2 .